Combined strategy of α 9-integrin transduction and AEIDGIEL peptide-functionalized fibrin gel biomaterials to promote mature DRG neurite growth - Anda Cimpean; Anda Cimpean; Lars Roll; Jacqueline Reinhard; Jessica C. F. Kwok; Jessica C. F. Kwok; Andreas Faissner; Fred de Winter; James W. Fawcett; James W. Fawcett; Pavla Jendelová (Frontiers in Cellular Neuroscience)
IntroductionSpinal cord injury involves complex pathobiological mechanisms, necessitating a multidimensional approach for its cure. Previous studies have shown that α9-integrin expression and activation in mature dorsal root ganglion neurons enable the regeneration of injured axons within the spinal cord. However, tissue cavitation and fibrosis impede the regenerating axons from following their usual pathways, forcing them to seek alternative routes rich in tenascin-C, the primary ligand of the integrin. Fibrin gel, an FDA-approved and biocompatible material, can offer three-dimensional support for axonal extension through the cavitated area, thus preventing the formation of aberrant paths and connections that occur in the absence of a suitable scaffold.MethodsThe aim of this study was to investigate how combining α9-integrin expression by adeno-associated virus with the use of a fibrin gel as an extracellular microenvironment affects the growth of mature DRG neurites in vitro. Additionally, we sought to functionalize fibrin with integrin ligand peptides, specifically AEIDGIEL, the active domain of tenascin-C, to ensure α9-integrin activation.ResultsOur results indicate that fibrin gels are a suitable biomaterial for promoting neurite growth and that AEIDGIEL peptide effectively activates the integrin. Furthermore, we corroborate an autocrine signaling loop of α9-integrin and TN-C produced by neurons.Discussionthe proposed combination therapy of α9-integrin and fibrin gel biomaterials incorporating AEIDGIEL peptide shows promise for addressing the complex challenges of spinal cord injury and promoting effective neural regeneration, laying the foundation for further in vivo research.